Environmental activism during communist era in Slovenia - Oset, Željko (Array, 2019)
Upon 1945, the Yugoslavian communist leadership put in motion ambitious strategy of industrialization and modernization regardless of costs, hence gradually evolving issues of environmental degradation were placed in a subservient position. Some planners deemed environmental degradation a necessary evil in order to fulfill pledges of development, progress, and better living standard. However, from the 1970s onwards environmental issues were addressed in urban planning, improvement of central-heating systems, by setting out emission thresholds, and mandatory environment clearance for credits approval for corporative entities, but law enforcement was not upheld to the highest standards and in full. The League of Communists of Slovenia allowed rather loosely knitted grass-roots environmental enthusiasts since the late 1960s; groups were comprised with well-educated citizens, which were mostly keen mountaineers. Environmentalists were especially active in urban areas mostly dealing with local issues (urban planning, sewage systems, contamination of the tap water, and excessive use of pesticides and fertilizers). In 1971, local environmental societies merged into the Association for Environmental Protection in Slovenia (AEPS), which in the late 1970s focused broadened scope of activities, mainly against the construction of hydroelectric power installations on the Soča River and the Mura River, and the Nuclear Power Plant Krško after the Chernobyl accident. In the 1970s, in Yugoslavia and Slovenia as well, concurrently with the West, modern legislation for environmental protection was adopted, and new self-government bodies for environmental issues comprising with politicians, lawyers, scientists, and environmentalists were established; thus the influence of AEPS somehow diminished.